LEGAL REVIEW OF THE POSITION OF ADOPTED CHILDREN IN INHERITING INHERITANCE BASED ON THE COMPILATION OF ISLAMIC LAW (KHI) IN INDONESIA - Yasinta Elka Prasastiningrum; Andoko , Andoko; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
Inheritance of property for adopted children in the Indonesian legal system is still a matter of debate due to the existence of legal pluralism that includes Islamic inheritance law, customary inheritance law, and civil inheritance law. In Islamic law, adopted children do not have inheritance rights because they do not have a blood relationship with their adoptive parents. However, in the Compilation of Islamic Law (KHI), adopted children can obtain a portion of the inheritance of their adoptive parents through the mandatory will mechanism, as regulated in Article 209 of the KHI, with a maximum limit of 1/3 of the total inheritance. This study aims to analyze the legal status of adopted children in the Islamic inheritance system in Indonesia and the implementation of the concept of wajibah will in court decisions. The case study used is the Decision of the Palembang Religious Court Number 2142/Pdt.G/2017/PA.Plg and the Decision of the Palembang High Religious Court Number 35/Pdt.G/2018/PTA.Plg. The results of the study indicate that at the first level, the Palembang Religious Court determined the adopted child as the heir, which is contrary to Islamic law. However, at the appeal level, the Palembang High Religious Court revised the decision by determining the adopted child as the recipient of the wajibah will of 1/6 of the inheritance of his adoptive parents. The application of mandatory wills in this case reflects the flexibility of Islamic law in Indonesia in accommodating developing social practices. Mandatory wills are a legal solution that bridges the need for protection of adopted children while still respecting the rights of biological heirs. Therefore, the existence of mandatory wills in the Islamic inheritance law system in Indonesia is a form of legal reform that aims to create justice and balance in the distribution of inheritance.